Hypothyroidism modifies lipid composition of polymorphonuclear leukocytes - Coria, Mariela J. (2012)
Thyroid hormones are important regulators of lipid metabolism. Polymorphonuclear leukocytes (PMN) are essential components of innate immune response. Our goal was to determine whether hypothyroidism affects lipid metabolism in PMN cells. Wistar rats were made hypothyroid by administrating 0.1 g/L 6-propyl-2-thiouracil (PTU) in drinking water during 30 days. Triacylglycerides (TG), cholesterol and phospholipids were determined in PMN and serum by conventional methods. The mRNA expression of LDL receptor (LDL-R), 3-hydroxy-3-methylglutaryl-CoA reductase (HMGCoAR), sterol regulatory element binding protein 2 (SREBP-2), and diacylglycerol acyltransferase 2 (DGAT-2) were quantified by Real-Time PCR. Cellular neutral lipids were identified by Nile red staining. We found hypothyroidism decreases serum TG whereas it increases them in PMN. This result agrees with those observed in Nile red preparations, however DAGT-2 expression was not modified. Cholesterol synthesizing enzyme HMGCoAR mRNA and protein was reduced in PMN of hypothyroid rats. As expected, cholesterol content decreased in the cells although it increased in serum. Hypothyroidism also reduced relative contents of palmitic, stearic, and arachidonic acids, whereas increased the myristic, linoleic acids, and the unsaturation index in PMN. Thus, hypothyroidism modifies PMN lipid composition. These findings would emphasize the importance of new research to elucidate lipid-induced alterations in specific function(s) of PMN.